Predictors of Hip Dysplasia at 4 Years in Children with Perinatal Risk Factors. Issue 1 (January 2021) - Humphry, Simon; Hall, Timothy; Hall-Craggs, Margaret A.; Roposch, Andreas
Abstract : Background: While perinatal risk factors are widely used to help identify those at risk for developmental dysplasia of the hip (DDH) within the first 6 to 8 weeks of life, limited data exist about their association with radiographic evidence of dysplasia in childhood. The purpose of this study was to determine which perinatal risk factors are associated with acetabular dysplasia in children who are ≥2 years of age. Methods: Pelvic radiographs were made in 1, 053 children (mean age, 4.4 years [range, 2 to 7 years]) who had been assessed prospectively as having at least 1 of 9 widely accepted perinatal risk factors for DDH. Two radiologists who were blinded to patient risk factors, history, and age determined the acetabular index (AI). The primary outcome was defined as an AI >2 standard deviations from the Tönnis reference values ("severe" dysplasia). The secondary outcome was an AI of >20° at >2 years of age. The association between risk factors and outcomes was assessed using logistic regression. The effect of treatment in infancy was adjusted for in 37 hips. Results: Twenty-seven participants (3%) showed "severe" hip dysplasia; 3 of these had received treatment for DDH in infancy. Girls were more likely to experience this outcome (odds ratio [OR] = 2.59; 95% confidence interval [CI] = 1.04 to 6.46; p = 0.04); no other examined risk factors were significant. The secondary outcome appeared in 146 participants (14%), 12 of whom had received treatment in infancy. We observed the following predictors for this outcome: female sex (OR = 1.77; 95% CI = 1.21 to 2.59; p = 0.003), breech presentation (OR = 1.74; 95% CI = 1.08 to 2.79; p = 0.02), and being a firstborn child, which had a protective effect (OR = 0.67; 95% CI = 0.46 to 0.96; p = 0.03). Conclusions: We identified a substantial number of cases that will require at least radiographic surveillance for mild and severe hip dysplasia; 92% had no prior diagnosis of DDH. Those who had been born breech were affected by this outcome even if ultrasonography of the hip had been normal at 6 to 8 weeks, suggesting a benefit from additional radiographic testing. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.